PENGARUH RANGE OF MOTION DAN BREATHING EXERCISE TERHADAP FATIGUE PADA PASIEN HEMODIALISIS - Intan, Erlena Nur; Putri Sulistyaningrum, Danny; Nafisah, Siti (NHM PRESS, 2024)
When the Kidney shows structural changes or dysfunction for more than three months, it may turn into chronic kidney failure. Worldwide, there are 1,5 million patients with chronic kidney failure receiving hemodialysis therapy. This prevalence increases by 8 percent per year. To overcome fatigue, nurses give a range of motion (ROM) and breathing exercises. This quantitative research determined the effects of the range of motion and breathing exercise on fatigue in patients receiving hemodialysis with a pre-experimental research design, involving two pretest-posttest control group designs. The sample consisted of 118 respondents taken with a total sampling technique. The Mann-Withney test showed than the influence of fatigue on the intervention and control groups after exercise range of movement and breathing was proven with the p-value is 0.000 (P<0.05). Therefore, future research can apply this research as a reference.